Instantaneous, room-temperature, open-air atmosphere, solution-phase synthesis of perovskite quantum dots through halide exchange employing non-metal based inexpensive HCl/HI: ensemble and single particle spectroscopy. Issue 9 (25th July 2019) - Mandal, Saptarshi; Roy, Debjit; De, Chayan K.; Ghosh, Swarnali; Mandal, Mrinal; Das, Ananya; Mandal, Prasun K.
Abstract : Instantaneous, room-temperature, open-air atmosphere, solution-phase synthesis of perovskite quantum dots. Abstract : Herein, the instantaneous synthesis of highly crystalline, uniform-sized ( ca. 11.3 ± 0.1 nm), blue-to-green to yellow to red-emitting all-inorganic perovskite quantum dots (CsPbBr3 and mixed halide PQDs) was achieved at room temperature under an open-air atmosphere (no glove box) through halide exchange in the solution phase employing easily available, inexpensive non-metal-based halide sources such as HCl and HI. No complicated pre-treatment of the halide source was required. Moreover, these PQDs were stable for a few weeks under an open-air atmosphere. The PL emission spectra are quite narrow, and the PLQYs are quite high (80% for even Br/I mixed PQDs). At the single particle level, the 〈ON fraction〉 has been noted to vary from 75% to 85% for different PQDs, the m ON values are close to 1.0, and the m OFF values are >1.5. The latter indicates that long ON durations are more probable. The increase in the ON event truncation time (from 2.7 to 4.0 s) and the concomitant decrease in the OFF event truncation time (from 6.6 to 4.3 s) could be correlated with the increase in the PLQY (from 0.55 to 0.75). In addition, an interesting memory effect could be observed in both the ON and the OFF event durations.